French Previously Untreated Patients with Severe Hemophilia A after Exposure to Recombinant Factor VIII : Incidence of Inhibitor and Evaluation of Immune Tolerance - Rothschild, C.; Laurian, Y.; Satre, E. P.; Derlon, A. Borel; Chambost, H.; Moreau, P.; Goudemand, J.; Parquet, A.; Peynet, J.; Vicariot, M.; Beurrier, P.; Claeyssens, S.; Durin, A.; Faradji, A.; Fressinaud, E.; Gaillard, S.; Guérin, V.; Guérois, C.; Pernod, G.; Pouzol, P.; Schved, J. F.; Gazengel, C. (Thrombosis and Haemostasis, 1998)
Fifty French previously untreated patients with severe hemophilia A (factor VIII <1%), treated with only one brand of recombinant factor VIII (rFVIII), were evaluated for inhibitor development, assessment of risk factors and outcome of immune tolerance regimen. The median period on study was 32 months (range 9-74) since the first injection of rFVIII. Fourteen patients (28%) developed an inhibitor, four of whom (8%) with a high titer (≥10 BU). All inhibitor patients but one continued to receive rFVIII either for on-demand treatment or for immune tolerance regimen (ITR). Among these patients, inhibitor was transient in 2 (4%), became undetectable in 6 and was still present in 6. The prevalence of inhibitor was 12%. Presence of intron 22 inversion was found to be a risk factor for inhibitor development. Immune tolerance was difficult to achieve in our series despite a follow-up period of 16 to 30 months: immune tolerance was complete in only one out of the 3 patients undergoing low dose ITR and in one out of the 5 patients with high dose ITR.